¿El capital social base de la economía social y solidaria? - Medina, Nancy (2023)
This article has been written based on work experience with associations of small farmers from the north central mountains of Ecuador, which showed the importance of social capital as living the valúes and principies for joint ventures sustainability of these organizations; in particular, valúes such as trust, built in the process, mutual aid and solidarity and reciprocity become backbone of efforts to enter the market together.